Revisiting Indonesian Nursing Students’ Needs and Perceptions on English Learning in Post-Pandemic Era - Santa Maya Pramusita; Komilie Situmorang; Bima Adi Saputra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
It is imperative to reassess the requirements of pupils in order to accurately understand their present circumstances, as the Covid-19 pandemic has significantly altered methods of teaching and learning. Given this circumstance, the researchers carried out a survey to determine the precise English language prerequisites of D3 nurses who are pursuing their bachelor's degree, in order to assess the level of importance for students and aid in the development of a suitable curriculum. The study utilized the technique developed by Hutchinson and Waters (1987) to investigate the specific English language requirements and sub-skills that nursing students need in order to effectively pursue their field of study in post COVID-19 era. In addition, the study examined the students' viewpoints on the pertinence of the courses offered to them. Data was gathered by employing questionnaires and conducting interviews. The study's findings suggest that the respondents' view of the full online English language courses they took had a significant impact on their professional growth as nurses. In addition, the participants demonstrated a significant degree of skill in Listening (Grand Mean = 4.1) and Reading (Grand Mean = 4.07) compared to Writing (Grand Mean = 3.97) and Speaking (Grand Mean = 3.92). The research findings suggest that the respondents consider English courses to be relevant. However, there is a need for improvement in the areas of Writing and Speaking.